Novel material for nickel recuperation - Rocha Filho, José A. Da [UNESP]; Bach, Erna E. [UNESP]; Barrak, Élcio R.; Queiroz, Alvaro A.a. De (ABM, ABC, ABPol, 2001)
Graft polymerization of N-vinyl-2-pyrrolidone with chitin was studied using hydrogen peroxide for initiation. The capacity of the obtained VP-g-Ch graft copolymer for adsorption of nickel was examined. The effect of temperature, pH and solute concentration on the chelating properties of the grafted and ungrafted chitin were determined. The thermal profiles obtained showed higher thermal resistance for the VP-g-Ch than chitin. The results indicate that the obtained graft copolymer under investigation is a potentially powerful ion exchanger that can be employed for heavy metals removal from wastewater effluents.
Keywords: chitin; grafted chitin; vinylpyrrolidone; nickel removal